Attitude of Primary Teachers towards Mid Day Meal Scheme - Pandey, Jyoti (THE PRIMARY TEACHER, 2016)
Cooked midday meal is mandatory to be provided to all children studying in government and government-aided primary and upper primary schools in all States of India. The Mid Day Meal Scheme (MDMS) was initiated on the adage that “when children have to sit with an empty stomach in class, they cannot focus on learning”. Children are the future of the country. Education and health are the two basic requirements of children. This study reveals the attitude of primary school teachers about the scheme. A total of 180 upper primary school teachers from Bareilly district of Uttar Pradesh were selected as sample and were given an attitude scale regarding the implementation of MDMS in their respective schools. It was found that the scheme has led to an increase in the enrolment and attendance rate in schools. Besides, it has contributed in retaining the classroom strength. However, it has adversely affected the teaching–learning process in schools as teachers have an additional burden of monitoring the supplies for the preparation of midday meals and overseeing their distribution among the students. Therefore, it is needed to clearly define the roles and responsibilities of teachers in the implementation of MDMS in schools.